2019
DOI: 10.1093/ajcn/nqz229
|View full text |Cite
|
Sign up to set email alerts
|

Human milk fatty acid composition is associated with dietary, genetic, sociodemographic, and environmental factors in the CHILD Cohort Study

Abstract: Background Fatty acids are a vital component of human milk. They influence infant neurodevelopment and immune function, and they provide ∼50% of milk's energy content. Objectives The objectives of this study were to characterize the composition of human milk fatty acids in a large Canadian birth cohort and identify factors influencing their variability. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
124
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(152 citation statements)
references
References 48 publications
12
124
14
2
Order By: Relevance
“…These findings were later supported by other studies that found that SNPs in the FADS gene cluster influence polyunsaturated fatty acid (PUFA) concentrations in human milk [106][107][108]. Together with a recently published study that found that mothers carrying the minor allele of FADS1 rs174556 had lower proportions of ARA [108], this finding strongly indicated that genetic variations affect human milk composition. Additionally, genetic variations in FADS and elongase (ELOVL) enzymes were shown to affect long chain PUFA (LC-PUFA) levels in human colostrum.…”
Section: Fatty Acid Desaturases (Fads) and Fatty Acid Composition In supporting
confidence: 53%
See 1 more Smart Citation
“…These findings were later supported by other studies that found that SNPs in the FADS gene cluster influence polyunsaturated fatty acid (PUFA) concentrations in human milk [106][107][108]. Together with a recently published study that found that mothers carrying the minor allele of FADS1 rs174556 had lower proportions of ARA [108], this finding strongly indicated that genetic variations affect human milk composition. Additionally, genetic variations in FADS and elongase (ELOVL) enzymes were shown to affect long chain PUFA (LC-PUFA) levels in human colostrum.…”
Section: Fatty Acid Desaturases (Fads) and Fatty Acid Composition In supporting
confidence: 53%
“…This lower proportion could not be compensated for by dietary fish consumption [23]. These findings were later supported by other studies that found that SNPs in the FADS gene cluster influence polyunsaturated fatty acid (PUFA) concentrations in human milk [106][107][108]. Together with a recently published study that found that mothers carrying the minor allele of FADS1 rs174556 had lower proportions of ARA [108], this finding strongly indicated that genetic variations affect human milk composition.…”
Section: Fatty Acid Desaturases (Fads) and Fatty Acid Composition In mentioning
confidence: 61%
“…In light of this, variations in human milk fatty acid composition between individuals and populations have been attributed to cultural differences (such as diet and other lifestyle factors) (6)(7)(8)(9)(10) (11) and human genetic differences (12,13) amongst others. Human milk fatty acid composition can therefore reflect both dietary sources and endogenous biological synthesis of fatty acids (14)(15)(16)(17) .…”
Section: Introductionmentioning
confidence: 99%
“…Maternal parity was also associated with differential fatty acid content in bovids and humans, favoring primiparous mothers [26,27]. Another factor that can influence milk composition, as well as the milk yield, is genetic background and variation in the genes associated with fatty acid biosynthesis [28][29][30].…”
Section: Introductionmentioning
confidence: 99%